Reaching agreement on contribution behavior in different cultures: a public goods game with representatives in Japan and Germany - Isaak, Andrew; Schwieren, Christiane; Iida, Yoshio (Journal of behavioral and experimental economics, 2022)
We discuss the results of an experimental public good game with group representatives in Germany and Japan, societies with varying levels of individualism. Representatives are permitted to communicate with their constituencies, but not with other representatives. We focus on accountability between representative and his constituency and on the risk taken in the interaction between representatives. We find that in Germany, subjects more readily trust a stranger's cooperativeness, groups reach agreement faster and are quicker to discuss and formulate a strategy in pre-play communication vis-a-vis Japanese subjects, where group formation takes longer. Further, we find a stronger end effect in Germany than in Japan, where the period of play explains much less variance in contribution behavior. Our study contributes to our understanding of intercultural differences in group formation and behavior when small group representatives invest in the public good, with implications for cross-cultural management, negotiation and leadership. Our evidence on between-country differences seems to empirically validate Yuki's (2003) framework for group behavior. We hope that our findings will stimulate further enquiry into human group behavior from a cross-cultural perspective.
Gesehen am 18.08.2022